Effects of Lycium barbarum Polysaccharides on Immunity and the Gut Microbiota in Cyclophosphamide-Induced Immunosuppressed Mice - Wang, Ying; Sun, Mingyi; Jin, Hongyu; Yang, Jianbo; Kang, Shuai; Liu, Yue; Yang, Shuang; Ma, Shuangcheng; Ni, Jian (Frontiers in Microbiology, 2021)
The mechanism of immunoregulation by Lycium barbarum polysaccharides (LBP) was assessed by studying the effect of LBP on the immunity and the gut microbiota. LBP isolated and purified in this study was composed of nine monosaccharides, with an Mw 1207 kDa. LBP showed immunomodulatory activity in Cy-treated mice by restoring the damaged immune organs and adjusting the T lymphocyte subsets. We also found that LBP increased the diversity of the gut microbiota and the relative abundances of bacteria such as Rickenellaceae, Prevotellaceae, Bifidobacteriaceae and so on, which were positively associated with immune traits. In addition, Caco2 cells model was used to explore the intestinal absorption of LBP. Results showed that LBP was hardly absorbed in the intestine, which suggesting that most LBP may interact with gut microbiota. These findings suggest that the immune response induced by LBP is associated with the regulation of the gut microbiota.